RIGHTS, RULES, AND DEMOCRACY - Kay, University of Connecticut-School of Law, Estados Unidos, Richard S. (Espaço Jurídico Journal of Law [EJJL], 2012)
Abstract: Democracy require protection of certain fundamental rights, but can we expect courts to follow rules? There seems little escape from the proposition that substantive constitutional review by an unelected judiciary is a presumptive abridgement of democratic decision-making. Once we have accepted the proposition that there exist human rights that ought to be protected, this should hardly surprise us. No one thinks courts are perfect translators of the rules invoked before them on every occasion. But it is equally clear that rules sometimes do decide cases. In modern legal systems the relative roles of courts and legislators with respect to the rules of the system is a commonplace. Legislatures make rules. Courts apply them in particular disputes. When we are talking about human rights, however, that assumption must be clarified in at least one way. The defense of the practice of constitutional review in this article assumes courts can and do enforce rules. This article also makes clear what is the meaning of “following rules”. Preference for judicial over legislative interpretation of rights, therefore, seems to hang on the question of whether or not judges are capable of subordinating their own judgment to that incorporated in the rules by their makers. This article maintains that, in general, entrenched constitutional rules (and not just constitutional courts) can and do constrain public conduct and protect human rights. The article concludes that the value judgments will depend on our estimate of the benefits we derive from the process of representative self-government. Against those benefits we will have to measure the importance we place on being able to live our lives with the security created by a regime of human rights protected by the rule of law. Keywords: Democracy. Human Rights. Rules. Judicial Review.